Firm heterogeneity and exports in Portugal: identifying export potential - Torres, Frederico Oliveira (2019)
For Melitz (2003), the driving force behind a firm’s decision to export is productivity. If firms pass the productivity cut-off, they all export. Nonetheless, empirical studies show that a substantial share of high-productive firms do not export. Using a dataset that covers Portuguese non-financial firms, between 2010 and 2016, we assess which factors determine the export decision, besides productivity. According to our results, firm’s characteristics, such as size, turnover, import as well as export status, age, worker skills and knowledge agglomeration, are crucial in the process of internationalisation of firms.